An investigation of physicians' prescribing behaviors related to antidiabetic agents for Type 2 diabetes mellitus patients and associated factors in Taiwan. (2nd November 2022) - Chen, Xiao; Wang, Chih-Yuan; Ko, Yu
Abstract: Objectives: This study aimed to examine the factors that may influence physicians' choice of antidiabetic agents. In addition, we investigated physicians' decision-making process and treatment of T2DM patients with chronic kidney disease (CKD). Finally, we wanted to determine whether physicians knew the latest recommendations for T2DM treatment. Methods: The study was conducted as a cross-sectional survey using an online self-administered questionnaire to collect data from physicians in Taiwan. We enrolled licensed physicians who worked in hospitals or clinics with an average monthly T2DM patient load of 100 patients. Descriptive statistics, the independent samples t -test, and the Chi-square test were used for data analysis. Moreover, the association was examined between respondents' demographics and the proportion of respondents who answered each T2DM treatment question correctly. Results: A total of 986 invitations were sent out, and 324 completed questionnaires were received. The most important factors that may influence physicians' choice of antidiabetic agents in each factor category were major comorbidities of patients, coverage of insurance, guideline recommendations, cardiovascular disease benefit, and whether a drug is the brand-name drug, respectively. When choosing second-line antidiabetic agents for T2DM patients with CKD, the most common reasons for doing so were recommendations of clinical guidelines (83.6%) and patients' renal function (59.6%) while SGLT2is were respondents' most commonly chosen treatment. Respondents were more familiar with ADA recommendations for patients with certain major comorbidities than with the drugs' labeled indications. Moreover, physicians who were younger, female, specialty in diabetes, or working in medical centers were more likely to give correct answers to certain questions about ADA guidelines (all p  < .05). Conclusion: This study provides a better understanding of the influential factors, treatment choices, and reasoning related to physicians' prescribing of antidiabetic agents in Taiwan. In addition, knowledge gaps in various physician groups were identified.